Best Practices for The Interdisciplinary Rehabilitation Team: A Review of Mental Health Issues in Mild Stroke Survivors. (4th June 2018) - Terrill, Alexandra L.; Schwartz, Jaclyn K.; Belagaje, Samir R.
Abstract : Individuals with mild strokes are generally considered fully functional and do not traditionally receive rehabilitation services. Because patients with mild stroke are assumed to have a good recovery, they may have deficits in other areas, including mental health, that are not addressed. As a result, patients with mild stroke are unable to meet quality of life standards. In addition, healthcare professionals are likely unaware of the potential mental health issues that may arise in mild stroke. To address this gap in knowledge, we review the evidence supporting mental health evaluation and intervention in mild stroke. Specifically, we review comorbid diagnoses including depression, anxiety, fatigue, and sleep disturbances and their potential effects on health and function. Finally, we conclude with general recommendations describing best practice derived from current evidence.